2005
DOI: 10.1037/0096-3445.134.2.222
|View full text |Cite
|
Sign up to set email alerts
|

Lexical Information Drives Perceptual Learning of Distorted Speech: Evidence From the Comprehension of Noise-Vocoded Sentences.

Abstract: Speech comprehension is resistant to acoustic distortion in the input, reflecting listeners' ability to adjust perceptual processes to match the speech input. For noise-vocoded sentences, a manipulation that removes spectral detail from speech, listeners' reporting improved from near 0% to 70% correct over 30 sentences (Experiment 1). Learning was enhanced if listeners heard distorted sentences while they knew the identity of the undistorted target (Experiments 2 and 3). Learning was absent when listeners were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

59
626
11

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 463 publications
(696 citation statements)
references
References 95 publications
59
626
11
Order By: Relevance
“…In fact, just such a role for lexical context was explicitly suggested by McClelland and Elman [2]. And indeed, in accordance with this, several recent experiments [30][31][32][33][34][35] have demonstrated that lexical influences can also guide tuning of speech perception. When listeners heard a perceptually ambiguous /s/-/f/ sound at the end of an utterance that would be a word if completed with /s/, they identified the sound as /s/.…”
Section: Tuning Of Speech Perceptionmentioning
confidence: 56%
“…In fact, just such a role for lexical context was explicitly suggested by McClelland and Elman [2]. And indeed, in accordance with this, several recent experiments [30][31][32][33][34][35] have demonstrated that lexical influences can also guide tuning of speech perception. When listeners heard a perceptually ambiguous /s/-/f/ sound at the end of an utterance that would be a word if completed with /s/, they identified the sound as /s/.…”
Section: Tuning Of Speech Perceptionmentioning
confidence: 56%
“…Previous studies have found that presenting a disambiguating stimulus (i.e., text or intact speech) at the same time (Wild et al., 2012a) or immediately after (Clos et al., 2014; Davis et al., 2005; Hervais‐Adelman et al., 2012; Sohoglu et al., 2012) the presentation of distorted speech increases comprehension of distorted speech. The current results and those of our previous studies (Hakonen et al., 2016; Tiitinen et al., 2012) extend these findings by showing that improvements in comprehension last for at least tens of seconds.…”
Section: Discussionmentioning
confidence: 99%
“…These amplitude-modulated noise bands are then recombined to create the noise-vocoded signal (see ref. 56). Noise vocoding has been used for many years in speech research to investigate the role of detailed spectral structure (independent of pitch) in speech perception (43).…”
Section: Methodsmentioning
confidence: 99%